Occurrences of Calliphoridae (Diptera) on Pig Carcasses in the Dry Season in Thailand - Rungsri, Nattida; Suebpongsiri, Asst.Prof.Pol.Lt.Col. Sarit; Prommi, Assist.Prof.Dr. Taeng On (Journal of Food Health and Bioenvironmental Science, 2018)
Calliphorids are the first arthropods to colonize corpses; their composition and abundance vary according to location. They are used to estimate post-mortem intervals and surmise the relocation of corpses. This study was focused on Calliphoridae associated with pig carcasses in sheltered and unsheltered cages. Four domestic pig (Sus scrofa Linnaeus, 1758) carcasses were used to determine the Calliphoridae activity on carrion over a period of 30 days in the dry season (April 5 to May 4, 2016). Five decomposition stages were observed and a total of 23,440 Calliphoridae, belonging to 3 species [Chrysomya megacephala (Fabricius), C. rufifacies (Macquart) and C. nigripes (Aubertin)] were collected in this study. Decomposition was slightly faster on the carcass in unsheltered areas, as was the the number of Calliphoridae specimens, relative to sheltered carcasses. The relationship between environmental factors such as temperature in cages, relative humidity and the internal temperature of the carcasses (sheltered and unsheltered carcasses) were significantly correlated to the decompositions process and insect species (P<0.01). Chrysomya megacephala showed preference for a sunny area, whereas C. rufifacies preferred a shaded area. This study provides baseline information on the necrophilous fauna for estimating postmortem interval in cases of human death in Thailand.